Another Reform of Qualifications—but Qualifying for What?. Issue 1 (14th February 2013) - Pring, Richard
Abstract There are several changes to the system of qualifications and examinations at ages 16 and 17, including the new English Baccalaureate. There are many problems: the constant churn in new qualifications reduces their vale to higher education and to employers; they are implemented without proper trialling; the EBacc in particular narrows the learning experience. There is a need for a moratorium on change and for a long, hard look by a non‐politically partisan advisory committee on the development of a qualification system.